Study guides

Q: What is the factor to x squared plus 7x minus 18?

Write your answer...

Submit

Related questions

(x + 2)(x - 9)

2222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222

A factor is like this. Original :x^2 + 7x - 18 (( x squared plus six x minus 18) Factored: (x+9)(x-2) ((x plus nine times x minus two))

Since the problem has 4 terms, first you factor x cubed plus 9x squared, then you factor 2x plus 18. So when you factor the first two term, you would get x sqaured (x plus 9). Then when you factor the last two terms and you get 2 (x plus 9). Ypure final answer would be (x squared plus 2)(x plus 9)

5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5

That factors to (x - 3)(x + 6)

X2 + 3X - 18 Ask yourself, what two factors of - 18 add to 3? (X + 6)(X - 3) -----------------

If that's -18y2, the answer is (3x - 2y)(x + 9y)

I'm not sure this was notated correctly. As written, this is -11x plus or minus 18, which doesn't factor.

2(x - 3)(x - 3)

12 squared plus 18 squared is equal to 468.

(x - 3)(x - 18)

0 = 2m^2 - 2m + 36 0 = 2(m^2 - m + 18) 0 = m^2 - m + 18

2(4x - 3)(x + 3)

(x, y) = (-3, -3) or (3, 3)

x2 - 9x + 18 = (x - 3)(x - 6)

(x - 3)(x^2 + 6)

That doesn't factor neatly. Applying the quadratic formula, we find two real solutions: -6 plus or minus (3 times the square root of 2) x = -1.75735931288 x = -10.24264

Since minus a negative is the same as a plus, then 18 - (-18) is the same as 18+18 = 36

b= 10

18 + 12 + 0 - 4 - 10 = 16

If you're solving for b, then you use the quadratic formula to factor out b. In this case, b= -1/4 or -18/12

The given expression can be simplified to: 3X squared +27

9 + 2 + 30 - 5 + 18 - 19 = -1

18